Determination of the width of the top quark - Abazov, V. M. (2011)
We extract the total width of the top quark, Γt, from the partial decay width Γ(t→Wb) measured using the t-channel cross section for single top-quark production and from the branching fraction B(t→Wb) measured in tt̄ events using up to 2.3fb-1 of integrated luminosity collected by the D0 Collaboration at the Tevatron pp̄ Collider. The result is Γt=1.99-0.55+0.69GeV, which translates to a top-quark lifetime of τt=(3.3-0.9+1.3)×10 -25s. Assuming a high mass fourth generation b′ quark and unitarity of the four-generation quark-mixing matrix, we set the first upper limit on |Vtb′|<0.63 at 95% C.L. © 2011 American Physical Society.